Creeping of Al-Khabab Creates Al-Mutadarak - Ali Abdul-Hussein ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2020)
This research paper is devoted to create the term of ‘Creeping of Al-Khabab’ for describing one of the prosodic changes that come on the rhythm of Al-Mutadarak’s metre , as a term and concept. As the previous and contemporary views of those who interested in prosody did not provide an accurate view of its description, free from the anomaly of the prosodic rules that